Digital Marketing and Brand Image To Increase Consumer Purchase Interest - Taufik Zulfikar; Ine Aprianti; Eva Rachmawati (Jurnal Manajemen Industri dan Logistik, 2022)
The digital marketing implemented optimally will improve the positive perception of the consumer candidates so that it develops a strong brand image impacting at an interest in buying.  How the institution maximizes the digital marketing function and how the institution's brand in the mind of the candidates might influence the interest of the students to become the students of the institution have become the phenomenon interesting to research.  This research aims to assess the influence of digital marketing and brand image on buying in the students of tutoring institutions in Bandung.  The research method used in this research is multiple linear regression.  The analysis units used in this research are the students of tutoring institutions in Bandung.  The sample-taking way is done using simple random sampling.  The value of the coefficient 1 = 0.466 and 2 = 0.457 and the value of F value is 710.596. The result shows that digital marketing and brand image influence interest in buying both simultaneously and partially.